Synthesis of MOFs for carbon capture application - Chen, Yipei (2018)
The work in this thesis focuses on the synthesis of metal organic frameworks (MOFs) both in batch and continuous work. Improvements are made in both, compared to the previous research. Furthermore, post-modification experiments are conducted to advance the characteristics of end product. Also, their application as solid sorbents in carbon capture is investigated. In Chapter 1, the background of greenhouse gas emissions is reviewed and discussed, followed by the development of carbon capture technologies and different adsorbents used in post-combustion carbon capture. An introduction to metal organic frameworks is then presented, including a literature review of the research to date, and various synthesis methods including batch and continuous routes. The last part of this chapter presents a literature review on how pre-synthetic design and post-synthetic modification synthesis of MOFs can be achieved. The theories and introductions of the characterization techniques used in this thesis are discussed in detail in Chapter 2. Chapter 3 discusses a new batch method for the efficient synthesis of micro-sized HKUST-1 with high yield (84%) under mild conditions. Different activation methods are conducted in the washing process. Both ethanol and methanol are tested to remove the impurities in pores of the samples. Finally, the optimal sample of HKUST-1 achieved is shown to produce a relatively high surface area (1615 m2/g) with a CO2 adsorption of 8.1% (measured by TGA at 1 atm and 27 oC). A step increase in the surface area is made by immersing the powders into a solution consisting of NaCl, water and methanol. Nano scale HKUST-1 is synthesized by adding trimethylamine (TEA) solution with the organic ligand precursor. The reaction rate is accelerated with this case because TEA solution is able to deprotonate the trimesic acid (the organic ligand). The method for nano scale HKUST-1 synthesis is the focus of Chapter 4. Chapter 5 reports the continuous synthesis process of HKUST-1 and ZIF-8. This work builds on previous work at Nottingham. A counter-current Nozzle reactor is used in this work. The products were compared with commercial equivalents. Post-synthetic modification of HKUST-1 was made to improve the hydrophobicity of HKUST-1 to extend its resilience to breakdown in the presence of moisture. In Chapter 6, a hybrid material TiO2@ZIF-8 is synthesized using the same reactor. Different reactor configurations were also used to generate a range of different products that are then compared. To conclude, a summary of the work conducted in this thesis is presented in Chapter 7, followed by a discussion on potential future work.